2005
DOI: 10.1111/j.1471-0528.2005.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Asian experience in hysteroscopic sterilisation using the Essure permanent birth control device

Abstract: Objective  To present our initial experience in the use of the Essure permanent birth control device in a predominately Asian population. Design  A retrospective study. Setting  Minimally Invasive Surgery Unit, KK Women's and Children's Hospital, Singapore. Population  Eighty women seeking permanent birth control. Methods  From 22 June 2001, women who sought sterilisation were counselled with regards to the various options of permanent birth control. Informed consent for hysteroscopic sterilisation was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 8 publications
1
27
0
2
Order By: Relevance
“…The initial pressure setting selected was 200 mmHg which was further increased to 300 mmHg if the endometrium was thickened. The 200 mmHg pressure is higher than has been previously reported [5,13]. Anecdotally, the resultant increase in uterine distention can result in some minimal baroceptor-related discomfort for the patient; however, with adequate analgesia, this very transient effect is well tolerated.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The initial pressure setting selected was 200 mmHg which was further increased to 300 mmHg if the endometrium was thickened. The 200 mmHg pressure is higher than has been previously reported [5,13]. Anecdotally, the resultant increase in uterine distention can result in some minimal baroceptor-related discomfort for the patient; however, with adequate analgesia, this very transient effect is well tolerated.…”
Section: Discussionmentioning
confidence: 68%
“…The reported bilateral placement rate ranges from 81% [1] to 98% [2]. It has been suggested that the procedure be completed in the follicular phase to improve visualization of the tubal ostia, and thus the successful placement of the coils [3][4][5]. Alternatively, hormonal endometrial suppression with the oral contraceptive pill, a progestin, or leuprolide before the procedure has been proposed to improve visualization [6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of antispasmodics has not been shown to reduce the incidence of tubal spasm. However, in a recent study from Singapore a significant increase in placement rates and decreased mean operation time were seen when patients were pre-medicated with spasmolytics (hyoscine) [11].…”
Section: Discussionmentioning
confidence: 98%
“…Four studies included separate placement rates for study group subsets but did not supply overall placement rates, 7,17,21,29 thus, the total number of placements in both groups was divided by the total number of patients in each study. For one study 61 only one group was included because the second group met the current review's exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Some explanations for placement success include procedure-related factors such as an in-patient setting, 16,21 a shorter procedure time, 3 greater provider experience, 3,5 and various types of medications and medication procedures. 3,5,7,21,22,29,38,47 Placement success associated with patient-related factors include prior use of an intrauterine device (IUD), 13 a history of sexually transmitted infections (STIs), 33 a lower body mass index (BMI), 11 and follicular phase of the menstrual cycle. 8,11,22 To date, there are no systematic analyses of variables associated with placement rates.…”
Section: Introductionmentioning
confidence: 99%